ADAM (a Disintegrin and Metalloproteinase) 15 Deficiency Exacerbates Ang II (Angiotensin II)–Induced Aortic Remodeling Leading to Abdominal Aortic Aneurysm. Issue 8 (August 2020) - Jana, Sayantan; Chute, Michael; Hu, Mei; Winkelaar, Gerrit; Owen, Caroline A.; Oudit, Gavin Y.; Kassiri, Zamaneh
Abstract : Objective: ADAM (a disintegrin and metalloproteinase) 15—a membrane-bound metalloprotease from the ADAM (disintegrin and metalloproteinase) family—has been linked to endothelial permeability, inflammation, and metastasis. However, its function in aortic aneurysm has not been explored. We aimed to determine the function of ADAM15 in the pathogenesis of aortic remodeling and aneurysm formation. Approach and Results: Male Adam15 -deficient and WT (wild type) mice (10 weeks old), on standard laboratory diet, received Ang II (angiotensin II; 1.5 mg/kg per day) or saline (Alzet pump) for 2 or 4 weeks. Ang II increased ADAM15 in WT aorta, while Adam15 -deficiency resulted in abdominal aortic aneurysm characterized by loss of medial smooth muscle cells (SMCs), elastin fragmentation, inflammation, but unaltered Ang II–mediated hypertension. In the abdominal aortic tissue and primary aortic SMCs culture, Adam15 deficiency decreased SMC proliferation, increased apoptosis, and reduced contractile properties along with F-actin depolymerization to G-actin. Ang II triggered a markedly greater increase in THBS (thrombospondin) 1 in Adam15 -deficient aorta, primarily the medial layer in vivo, and in aortic SMC in vitro; increased SSH1 (slingshot homolog 1) phosphatase activity and cofilin dephosphorylation that promoted F-actin depolymerization and G-actin accumulation. rhTHBS1 (recombinant THBS1) alone was sufficient to activate the cofilin pathway, increase G-actin, and induce apoptosis of aortic SMCs, confirming the key role of THBS1 in this process. Further, in human abdominal aortic aneurysm specimens, decreased ADAM15 was associated with increased THBS1 levels and loss of medial SMCs. Conclusions: This study is the first to demonstrate a key role for ADAM15 in abdominal aortic aneurysm through regulating the SMC function, thereby placing ADAM15 in a critical position as a potential therapeutic target for abdominal aortic aneurysm. Abstract : Supplemental Digital Content is available in the text.